The Relationship Between a Baby's Age and Sleepiness in a Sample of Mothers - Sánchez-García, Mar; Cantero, María José; Carvajal-Roca, Eva (Frontiers in Psychology, 2021)
The birth of a child marks the beginning of a new evolutionary phase for their parents. Although many of these changes are positive, there is a negative side to them, such as how the time and quality of a night’s sleep are reduced during this phase. Nevertheless, despite how common this problem is, there is a lack of information on how long it lasts, with estimations ranging from 3 months to 6 years. This study assessed the sleep problems of a sample of Spanish women with babies under 2 years of age and compared the results with another sample of women of similar characteristics who were not looking after a child at that moment. The results show that sleep deprivation and other related problems seem to persist until at least the third semester after the birth.